1994
DOI: 10.1029/94jd00621
|View full text |Cite
|
Sign up to set email alerts
|

Physical and optical properties of the Pinatubo volcanic aerosol: Aircraft observations with impactors and a Sun‐tracking photometer

Abstract: As determined in situ by impactor samplers flown on an ER‐2 at 16.5‐ to 20.7‐km pressure altitude and on a DC‐8 at 9.5‐ to 12.6‐km pressure altitudes, the 1991 Pinatubo volcanic eruption increased the particle surface area of stratospheric aerosols up to 50‐fold and the particle volume up to 2 orders of magnitude. Particle composition was typical of a sulfuric acid‐water mixture at ER‐2 altitudes. Ash particles coated with sulfuric acid comprised a significant fraction of aerosol at DC‐8 altitudes. Mie‐compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 11 publications
7
110
0
Order By: Relevance
“…Although volcanic aerosol is often best described by multi-modal size distributions (e.g. Pueschel et al, 1994), we restricted the simulations to a single mode with a width of 1.6 for simplicity. The median radius and the number concentration were varied to cover a wide range for each particle type.…”
Section: Simulation Setupmentioning
confidence: 99%
See 4 more Smart Citations
“…Although volcanic aerosol is often best described by multi-modal size distributions (e.g. Pueschel et al, 1994), we restricted the simulations to a single mode with a width of 1.6 for simplicity. The median radius and the number concentration were varied to cover a wide range for each particle type.…”
Section: Simulation Setupmentioning
confidence: 99%
“…In Table 5 the largest possible range is highlighted. Pueschel et al (1994) reported a single aerosol particle mode around 0.1 µm in the UTLS region for background conditions. After volcanic eruptions, they found a second, larger mode around 0.4 µm due to enhanced sulfate aerosol and a third mode around 0.8 µm containing volcanic ash particles.…”
Section: Sulfate Aerosol Simulationsmentioning
confidence: 99%
See 3 more Smart Citations